Cybersecurity Issues in Generative AI - Oh, Subin; Shon, Taeshik (2023 International Conference on Platform Technology and Service, PlatCon 2023 - Proceedings, 2023)
Generative AI technology is being applied in various fields. However, the advancement of these technologies also raises cybersecurity issues. In fact, there are cases of cyber attack using Generative AI, and the number is increasing. Therefore, this paper analyzes the potential cybersecurity issues associated with Generative AI. First, we looked at the fields where Generative AI is used. Representatively, Generative AI is being used in text, image, video, audio, and code. Based on these five fields, cybersecurity issues that may occur in each field were analyzed. Finally, we discuss the obligations necessary for the future development and use of Generative AI.
Keywords: AI Technologies; Cyber security; Cyber-attacks; Generative AI; Generative model; Paper analysis; Text images; Video codes; Cybersecurity; Generative AI; Generative Models